STRUKTUR ARGUMEN DALAM WACANA KARYA TULIS ILMIAH MAHASISWA - Ardianto Ardianto (LITERA, 2015)
This study aims to describe argument structures based on types of complexity andconclusion drawing in students’ academic writing discourse. It employed the qualitativedescriptive approach using the communication content analysis method. The datasources were undergraduate theses written by students of the Department of Tarbiyah,STAIN Manado. The results of the study are as follows. First, the argument structuresbased on types of complexity comprise a simple argument structure and a complexargument structure. The complex argument structure consists of an adjacent argumentstructure and a multi-layer argument structure. Second, the argument structures based onconclusion drawing consist of an inductive argument structure and a deductive argumentstructure.